2008
DOI: 10.1029/2007jd009753
|View full text |Cite
|
Sign up to set email alerts
|

Influence of El Niño–Southern Oscillation on the interannual variability of tropospheric ozone in the northern midlatitudes

Abstract: [1] We use the Goddard Earth Observing System Chem (GEOS-Chem) model to interpret long-term measurements of tropospheric ozone (O 3 ) and carbon monoxide (CO) and to investigate the factors that contribute to their interannual variation (IAV) during the period from 1987 to 2005. The model reproduces relatively well the observed IAV of CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
109
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 95 publications
(125 reference statements)
7
109
2
Order By: Relevance
“…For instance, a simulation over 1987-2005 with assimilated meteorology but a parameterized stratospheric ozone source was unable to match the observed interannual variability of extratropical ozone (Koumoutsaris et al, 2008). Furthermore, the interannual variability (standard deviation) of midtropospheric ozone derived from ozonesonde and aircraft measurements is three times larger than that simulated in a CTM with a parameterized stratospheric ozone source (Hess and Zbinden, 2013).…”
Section: State Of Knowledgementioning
confidence: 95%
See 2 more Smart Citations
“…For instance, a simulation over 1987-2005 with assimilated meteorology but a parameterized stratospheric ozone source was unable to match the observed interannual variability of extratropical ozone (Koumoutsaris et al, 2008). Furthermore, the interannual variability (standard deviation) of midtropospheric ozone derived from ozonesonde and aircraft measurements is three times larger than that simulated in a CTM with a parameterized stratospheric ozone source (Hess and Zbinden, 2013).…”
Section: State Of Knowledgementioning
confidence: 95%
“…Furthermore, the interannual variability (standard deviation) of midtropospheric ozone derived from ozonesonde and aircraft measurements is three times larger than that simulated in a CTM with a parameterized stratospheric ozone source (Hess and Zbinden, 2013). Both models in these studies were unable to reproduce the observed lowozone anomaly following the 1991 Pinatubo volcanic eruption, although they do capture some aspects of the observed 1998-1999 high-ozone anomaly at northern mid-latitudes, which was associated at least in part with an increase in the STT ozone flux following the 1997-8 El Niño (Koumoutsaris et al, 2008;Hess and Zbinden, 2013). A few studies show that CTMs with a climatological stratosphere underestimate observed ozone abundances at high northern latitudes in winter-spring (Hu et al, 2017) and in stratospheric intrusions that penetrate into the lower troposphere (Hudman et al, 2004;Zhang et al, 2011).…”
Section: State Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, changes in emissions, especially biomass burning, associated with ENSO affect the ozone burden across the tropics . ENSO has also been linked to column ozone changes above Europe with positive anomalies of tropospheric ozone column and surface ozone occurring in the spring following an El Niño year, for a variety of reasons including changes in STE, biomass burning emissions and pollution transport pathways from Asia and North America (Koumoutsaris et al, 2008). Voulgarakis et al (2010) used a global chemical transport model to determine the interannual variability in the global tropospheric ozone burden for the period 1996-2000, which included the strong El Niño event of 1997-1998.…”
Section: Climate Variabilitymentioning
confidence: 99%
“…during the O 3 recovery after Pinatubo's eruption in 1991, followed by the global anomaly subsequent to the extreme El-Niño event of 1997 (Koumoutsaris et al, 2008).…”
mentioning
confidence: 99%